Coarse wavelength division multiplexing technologies and applications - Thiele, Hans-Jörg; Nebeling, Marcus (Optical science and engineering (CRC Press), 2007)
Investigates the historical development and component technology that have made coarse wavelength division multiplexing (CWDM) a successful commercial technology. This book explains what CWDM is, how it is achieved, and why it should be deployed. It also includes practical usage in metro, CATV, and fiber to the premises networks.